Allopurinol use and type 2 diabetes incidence among patients with gout: A VA retrospective cohort study. Issue 35 (28th August 2020) - Slobodnick, Anastasia; Toprover, Michael; Greenberg, Jeffrey; Crittenden, Daria B.; Pike, Virginia C.; Qian, Yingzhi; Zhong, Hua; Pillinger, Michael H.
Abstract : Abstract: To assess the impact of allopurinol on diabetes in a retrospective cohort of Veterans' Affairs patients with gout. The New York Harbor VA computerized patient record system was searched to identify patients with an ICD-9 code for gout meeting at least 4 modified 1977 American Rheumatology Association gout diagnostic criteria. Patients were divided into subgroups based on >30 continuous days of allopurinol, versus no allopurinol. New diagnoses of diabetes, defined according to American Diabetes Association diagnostic criteria or clinical documentation explicitly stating a new diagnosis of diabetes, were identified during an observation period from January 1, 2000 through December 31, 2015. Six hundred six gout patients used allopurinol >30 continuous days, and 478 patients never used allopurinol. Over an average 7.9 ± 4.8 years of follow-up, there was no significant difference in diabetes incidence between the allopurinol and non-allopurinol groups (11.7/1000 person-years vs 10.0/1000 person-years, P  = .27). A lower diabetes incidence in the longest versus shortest quartiles of allopurinol use (6.3 per 1000 person-years vs 19.4 per 1000 person-years, P <.0001) was attributable to longer duration of medical follow-up. In this study, allopurinol use was not associated with decreased diabetes incidence. Prospective studies may further elucidate the relationship between hyperuricemia, gout, xanthine oxidase activity, and diabetes, and the potential impact of gout treatments on diabetes incidence. Abstract : Supplemental Digital Content is available in the text